AB0975 Power and Colour Doppler Findings in Lower Extremity Entheses of Healthy Children – Effect of Measurement Distance from Bone and Joint Position. (10th June 2014) - Roth, J.; Di Geso, L.
Abstract : Background: Musculoskeletal ultrasound has significant potential in the assessment of the pediatric entheses. Doppler signals at the site of tendon insertions are often considered as signs of pathology for enthesitis as well as apophysitis. The normal pediatric enthesis can nevertheless exhibit Doppler signals as well and this might be especially relevant during periods of rapid growth with increased mechanical strain. Limited and partially confliciting data is available for Doppler charactistics of the normal pediatric enthesis. This may be due to technical factors, variable definitions of the anatomic location of the enthesis and variable positioning of the patient. Objectives: The aim of this study was to examine relevant entheses of the knee and ankle joint in healthy children at the peak of linear growth and determine the effect of measurement distance from the insertion and position of the joint. Methods: 35 males and females with an age range of 11-14 years volunteered for this study. All participants were free of musculoskeletal symptoms, medical conditions or medication affecting the MSK system, MSK injuries in the past three months and did not participate in sports more than three times per week. The Insertion of the Quadriceps tendon into the patella, the proximal and distal patella tendon insertion and the Achilles tendon insertion were examined with standardized settings in Power as well as Colour Doppler Ultrasound using an Esaote Mylab 70 XVG Gold machine with a linear probe ranging from 6 to 18 MHz. Both extremities were assessed in neutral as well as 30 degrees flexion. All images were acquired by a single examiner and read by two readers. A subset of volunteers was reassessed 2 days later. On all images the presence of Doppler signals was assessed directly at the bone/cartilage interface as well as within a distance of 2mm, 5mm and 10mm. Results: No Doppler signals were seen directly at the bone/cartilage surface in any of the enthesis. The highest prevalence of signals was found in the quadriceps tendon. Comparing neutral with 30 degrees flexion 30% vs. 40% of participants displayed Doppler signals within 10 mm of the insertion, 30% vs. 35% within 5 mm and 20% vs. 10% within 2 mm. A similar percentage of Doppler signals was seen within 2 mm of the tibial tuberosity although with 10% of volunteers displaying signals in neutral vs 20% in flexed position. At 10 mm distance these percentages were 30% in flexed vs 20% in neutral position. In contrast no Doppler signals were seen at the insertion of the proximal Patella tendon and the Achilles tendon. No significant differences were seen between Colour and Power Doppler. Conclusions: The specificity of Doppler findings in Apophysitis or Enthesitis is expected to be much higher in the proximal Patella tendon and Achilles tendon than in other entheses. At all Entheses Doppler signals very close to the bone/cartilage surfaces are rarely observed in healthy children. In contrast, the tendon insertions at the proximal patella and the tibial tuberosity display a high prevalence of Doppler signals at a distance of more than 2 mm from the insertion possibly related to mechanical strain occurring physiologically. In order to increase sensitivity the exam should be performed in various positions of the joint. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3404